DAMPAK VARIABEL MAKRO EKONOMI TERHADAP PERMINTAAN PEMBIAYAAN MURABAHAH PERBANKAN SYARIAH - Dwijayanty, Rima (Program Studi Akuntansi FPEB UPI, 2017)
Abstract. This research was conducted to to determine the effect of macroeconomic variables on the demand for Islamic banking murabaha financing, so as to provide an explanation that in this case the rate of inflation, exchange rate, and the BI rate has an influence on murabaha financing demand.This research uses secondary data from Indonesian Banking Statistics and Sharia Indonesian Banking Statistics from period of January 2010 until Desember 2015 using verificative and descriptive methods. Analyze is using multiple regression with EViews. The result shows simultaniously macroeconomic variables affect simultaneously on murabaha financing demand. While partial variabel Rate of Inflation and Exchange rate positively influence significantly to murabaha financing demand. Meanwhile BI Ratenegatively influence significantly to murabaha financing demand.